Barriers and facilitators for treatment-seeking for mental health conditions and substance misuse: multi-perspective focus group study within the military. Issue 6 (25th November 2020) - Bogaers, Rebecca; Geuze, Elbert; van Weeghel, Jaap; Leijten, Fenna; van de Mheen, Dike; Varis, Piia; Rozema, Andrea; Brouwers, Evelien
Abstract : Background: Globally, millions are exposed to stressors at work that increase their vulnerability to develop mental health conditions and substance misuse (such as soldiers, policemen, doctors). However, these types of professionals especially are expected to be strong and healthy, and this contrast may worsen their treatment gap. Although the treatment gap in the military has been studied before, perspectives of different stakeholders involved have largely been ignored, even though they play an important role. Aims: To study the barriers and facilitators for treatment-seeking in the military, from three different perspectives. Method: In total, 46 people participated, divided into eight homogeneous focus groups, including three perspectives: soldiers with mental health conditions and substance misuse ( n = 20), soldiers without mental health conditions and substance misuse ( n = 10) and mental health professionals ( n = 16). Sessions were audio-taped and transcribed verbatim. Content analysis was done by applying a general inductive approach using ATLAS.ti-8.4.4 software. Results: Five barriers for treatment-seeking were identified: fear of negative career consequences, fear of social rejection, confidentiality concerns, the 'strong worker' workplace culture and practical barriers. Three facilitators were identified: social support, accessibility and knowledge, and healthcare within the military. The views of the different stakeholder groups were highly congruent. Conclusions: Barriers for treatment-seeking were mostly stigma related (fear of career consequences, fear of social rejection and the 'strong worker' workplace culture) and this was widely recognised by all groups. Social support from family, peers, supervisors and professionals were identified as important facilitators. A decrease in the treatment gap for mental health conditions and substance misuse is needed and these findings provide direction for future research and destigmatising interventions.